Scientometrics assessment of Malaysian social science research in the web of science (2007-2017) / Siti Khairiha Ibrahim - Siti Khairiha , Ibrahim (2021)
Previous studies mostly have looked into the growth of science-based research and there has been limited empirical work carried to look into the research performance including publication productivity and impact of Malaysian Social Science Research Systems. Therefore, the purpose of this study is to explore the research performance using scientometric assessment of Malaysian Social Science Research in the Web of Science (WoS) over the period of 11 years from 2007 to 2017 at the meso and micro levels. This study covers the discipline's productivity, impact and publication patterns. The research questions posed are (a) What is the growth of Malaysian Social Science Research literature in the Web of Science over the period of 2007 - 2017? (b) What is the scientific performance of Malaysian Social Science Research in the Web of Science at the meso and micro level? (c) What is the research impact of Malaysian Social Science Research in the Web of Science at the meso and micro level? and (d) What are the characteristics of the journals that Malaysian Social Science researchers published in? A total of 9929 publications retrieved from the Web of Science Core Collection database over the period of 2007 to 2017 covered in the Social Science Citation Index (SSCI) is used for to answer the research questions posed. Based on search criteria used which is “Malaysia” in address and “Article” in type of document, 6249 records were retrieved and used for analysis. The analysis of trends, profiles in publication and citation patterns explore the strength of different research areas. The findings indicate that the publication of Malaysian Social Science research in the WoS has been increasing since 2008. The most productive institution and social scientist are both from the Universiti Malaya. University Tunku Abdul Rahman has the highest total citation per paper over the period of study. One of the characteristics of WoS indexed journals that published Malaysian Social Science research is obviously the international commercial publishers as the coverage of Malaysian social science journals in WoS is only limited to the Malaysian Journal of Library & Information Science. The finding of this study found that the overall publication and citation of Malaysian Social Science research in the WoS have a positive growth in the duration of the study. The study may provide a better insight of research evaluation decision in terms of the award of research grant, staff promotion and staff recruitment considering publications in the core literature.